A highly productive mixotrophic fed-batch strategy for enhanced microalgal cultivation. Issue 11 (11th May 2022) - Figueroa-Torres, Gonzalo M.; Pittman, Jon K.; Theodoropoulos, Constantinos
Abstract : A highly productive fed-batch cultivation strategy is presented, that consists of intermittent pulses of organic carbon that promotes mixotrophic microalgal growth whilst favouring starch and lipid formation. Abstract : Microalgal biomass offers great opportunities for green energy generation within emerging biorefinery frameworks. However, the conventional cultivation of microalgae in phototrophic batch systems, which typically yield low biomass productivities, is unfit for large-scale applications. Fed-batch cultivation, on the other hand, represents a more reliable strategy for sustained biomass growth. This work presents a highly productive fed-batch cultivation strategy consisting of intermittent pulses of organic carbon that promotes microalgal growth in mixotrophic mode whilst favouring the formation of starch and lipid metabolites, which have various applications for fuel and high value-added chemicals. Using a combined experimental and modelling approach, the fed-batch pulse feeding regime was additionally optimised for maximal starch and lipid formation, resulting in a 3-pulse strategy which yielded substantial increases of 94% biomass, 676% starch, and 252% lipids with respect to a standard batch scenario. This fed-batch strategy represents a promising cultivation strategy fit for sustainable biofuel production.